A structural framework for DNA replication and transcription through chromatin. (December 2021) - Willhoft, Oliver; Costa, Alessandro
Abstract: In eukaryotic cells, DNA replication and transcription machineries uncoil nucleosomes along the double helix, to achieve the exposure of the single-stranded DNA template for nucleic acid synthesis. The replisome and RNA polymerases then redeposit histones onto DNA behind the advancing molecular motor, in a process that is crucial for epigenetic inheritance and homeostasis, respectively. Here, we compare and contrast the mechanisms by which these molecular machines advance through nucleosome arrays and discuss how chromatin remodellers can facilitate DNA replication and transcription.